PENDEKATAN PEMBANGUNAN BERKELANJUTAN DALAM PERENCANAAN PEMBANGUNAN DESA: (Studi di Kecamatan Alok Kabupaten Sikka) - Marianus Mario Belawa Keraf (Jurnal Administrasi Publik, 2022)
To achieve sustainable development goals in village development planning activities an ideal development approach is needed. One development approach that can be used is the socio-cultural sustainability approach. The socio-cultural sustainability approach is expressed in three ways, namely social justice, human dignity, and human quality of life. In implementing the objectives of the socio-cultural sustainability approach with the values of social justice, human dignity, and quality of human life, the implementation did not go well and encountered various obstacles. Obstacles found included human resources, community culture, and habits, domination of village elites in decision-making, and improving the quality of life was only assessed with economic and social values without regard for environmental values. Therefore, it requires commitment and cooperation from all stakeholders in the village and parties related to village development planning activities so that the achievement of sustainable development goals in the village can be realized.